Система Український глосарій як база знань про українське слово та інструмент лексикографа - Karpilovs’ka, Evheniia (Wiener Slawistischer Almanach, 2023)
This article deals with the structure, the data corpus, and the theoretical and practical importance of the “Ukrainian glossary“ computer system based at the Institute for the Ukrainian Language of the National Academy of Sciences of the Ukraine in Kyiv. The system provides tools for the analysis and synthesis of the morphemic structure of word forms, for the creation of specialized dictionaries of morphemes (roots, prefixes, suffixes, infixes, interfixes), for research into models of morphemic word structure, and for word nests and nest models in general. The system has an interface that allows searches for word forms using several parameters (form, semantics, presence in texts and in registers of morphemic and word formation dictionaries). The ”Ukrainian glossary“ performs informational-advisory, educational. and research functions.